2011
DOI: 10.1097/yco.0b013e328346176e
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on intellectual disability in Taiwan

Abstract: As a result of this review process, this paper suggests that future study should focus on an evaluation of the efficacy of current health and social policies related to people with intellectual disability, and that supportive health environments be initiated for this group of people living in institutions or in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…These results support increasing research pointing to the reduced access of disabled persons to the needed oral health care services due to various barriers such as the disabled person's inability to communicate their symptoms and poor cooperation with treatment. [101141] Previous studies have also reported similar findings. Compared with representative data on the oral health of German adults, individuals with intellectual disabilities had more extracted teeth than normal adults,[42] and the same was reported among German athletes with ID.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These results support increasing research pointing to the reduced access of disabled persons to the needed oral health care services due to various barriers such as the disabled person's inability to communicate their symptoms and poor cooperation with treatment. [101141] Previous studies have also reported similar findings. Compared with representative data on the oral health of German adults, individuals with intellectual disabilities had more extracted teeth than normal adults,[42] and the same was reported among German athletes with ID.…”
Section: Discussionsupporting
confidence: 61%
“…[3456789] Individuals with intellectual disabilities may suffer more from the consequences of oral disease than those without any intellectual disabilities due to their inability to accurately communicate their symptoms and their caregivers’ inability to appraise their oral health condition. [1011]…”
Section: Introductionmentioning
confidence: 99%
“…[9] In addition, the demand for dental care can often be limited either by the disabled individual's incapacity to accurately convey their symptoms or by the parent or caregivers to evaluate their oral condition. [10]…”
Section: Introductionmentioning
confidence: 99%